2021
DOI: 10.1101/2021.03.18.435935
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting intelligence from fMRI data of the human brain in a few minutes of scan time

Abstract: A number of recent studies have investigated machine learning techniques for predicting individual behaviour from fMRI. Even though encouraging results have been obtained, excessive scan times – especially in resting state fMRI – are a limiting factor.Here we present a new machine learning algorithm for predicting individual behaviour of healthy human subjects using both resting state (rsfMRI) as well as task-based fMRI (tfMRI). It achieves dimensionality reduction via ensemble learning and partial least squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…In the case of the HCP dataset, the statistically significant age bias of the “raw” model for predicting fluid intelligence is in line with previous findings [ 18 , 19 ] and could likely exaggerate to a serious bias when testing the model on data of participants outside of the—relatively narrow—age range of the HCP sample. In this case, the bias would likely significantly harm the out-of-sample generalizability of this model.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the case of the HCP dataset, the statistically significant age bias of the “raw” model for predicting fluid intelligence is in line with previous findings [ 18 , 19 ] and could likely exaggerate to a serious bias when testing the model on data of participants outside of the—relatively narrow—age range of the HCP sample. In this case, the bias would likely significantly harm the out-of-sample generalizability of this model.…”
Section: Discussionsupporting
confidence: 86%
“…Functional connectivity data from the Human Connectome Project [ 55 ] (HCP) were used to build predictive models of fluid intelligence ( G f ) and to test for the previously discussed confounding effect of age [ 18 , 19 ] and, additionally, the—somewhat underdiscussed—batch-like effect of acquisition date of the data within the course of the data acquisition process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FRC and ORC have also been applied to brain networks of healthy populations. Specifically, Lohmann et al [42] applied FRC to predict the intelligence of healthy human subjects using fMRI data, and Farooq et al [36] applied ORC to identify changes in brain structural connectivity during healthy aging. However, no previous study has assessed the ability of discrete Ricci curvatures to characterize FCN alterations during healthy aging.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chatterjee et al [48] used a version of FRC to determine the changes in brain functional connectivity related to attention deficit hyperactivity disorder (ADHD). Additionally, FRC has been used to analyze task-based fMRI data [49] as well as to predict intelligence of healthy human subjects [50]. Most of these studies have also contrasted graph Ricci curvatures with standard network measures such as clustering coefficient and node betweenness centrality, and showed that graph Ricci curvatures can provide new information about brain connectivity organization.…”
Section: Introductionmentioning
confidence: 99%